SYNTHESIS OF 3,5,7,3'- TETRAMETHOXY -4'-HYDROXY-8-C-P RENYLFLAVONE: Short Communication (Biological Sciences - PJSIR, 2002)
in dry acetone (25 ml), methoxymethyl chloride (1,0.5g) and anhydrous potassium carbonate (10 g) was refluxed for about 3 h. Usual work up and it was crystallized from benzene, m.p. 68°C; (M+, 240); IR: 1642, 1603, 1598, 1400, 1380, 1364, 1214,1200, 1040, 980 cm- 1; 1H-NMR: 2.48 (s, 3H,-COCH), 3.42 (s,3H, -CHpC)3.98 and 4.00 (2s, 6H, -OCXz), 5.55 (s, 2H,-CHpC), 6.41 (s, lH,H-3), 7. 12 (s, lH, H-5).